O+囗=45 O=( ) 囗+ ☆=62 囗= ( ) ☆ +O=43 ☆= ( ) (2)囗+O=400 O=( ) 囗= O+O+O+O+ 囗

来源:学生作业帮助网 编辑:六六作业网 时间:2024/05/28 04:18:03
O+囗=45O=()囗+☆=62囗=()☆+O=43☆=()(2)囗+O=400O=()囗=O+O+O+O+囗O+囗=45O=()囗+☆=62囗=()☆+O=43☆=()(2)囗+O=400O=()囗

O+囗=45 O=( ) 囗+ ☆=62 囗= ( ) ☆ +O=43 ☆= ( ) (2)囗+O=400 O=( ) 囗= O+O+O+O+ 囗
O+囗=45 O=( ) 囗+ ☆=62 囗= ( ) ☆ +O=43 ☆= ( ) (2)囗+O=400 O=( ) 囗= O+O+O+O+ 囗

O+囗=45 O=( ) 囗+ ☆=62 囗= ( ) ☆ +O=43 ☆= ( ) (2)囗+O=400 O=( ) 囗= O+O+O+O+ 囗
(1)O+囗=45 O=(13 ) 囗+ ☆=62 囗= ( 32) ☆ +O=43 ☆= ( 30)
(2)囗+O=400 O=(80 ) 囗= O+O+O+O 囗=(320)